Une absence genrée - Laura Odasso (Revue des Mondes Musulmans et de la Méditerranée)
This article focuses on the notion of absence in the migratory trajectory of females of Mediterranean – Arab origin (Morocco and Lebanon) living in mixed couples in France. It shows how these women’s agency and a certain “gender doxa”, promoted by these women’s countries of origin, contribute to define the dialectic between presence and absence for both their migration and homemaking projects. The relation with the country of origin is expressed in the personal, family and cultural work that such women accomplish and produces specific absences. Two forms of absence have been identified: the first, an existential absence is caused by these women’s desire for emancipation and their effort to “do like everybody else” in the country of residence. The second absence is an institutional absence that arises from the policies of their countries of origin in matters of family and nationality rights. Existential absence is often temporary, while institutional absence varies according to each State and perpetrates gendered absences that are passed on to successive generations.